Analisis Kandungan Logam Berat Kromium (Cr) Pada Air, Sedimen Dan Kerang Hijau (Perna viridis) Di Perairan Trimulyo Semarang - Ria Azizah Tri Nuraini; Hadi Endrawati; Ivan Riza Maulana (Universitas Diponegoro, 2017)
Metal pollution becomes a problem that is very threatening to marine ecosystems. This is because heavy metals difficult be destroyed and will accumulate in the water. This study aims to determine the content of chromium (Cr) in Water, Sediment and green mussels (Perna viridis) and know the maximum limit weekly consumption and the feasibility of the Green Shellfish consumption. Samples were taken in January 2016 for Trimulyo waters. Research using descriptive methods. Sampling was done by purposive sampling method. Heavy metal content analysis using AAS. MTI Value (Maximum Tolerable Intact) is calculated by the formula MWI / Ct to determine the value of the maximum limit of consumption of green mussels per week. The results showed the content of chromium (Cr) in water in Trimulyo waters of <0.003 mg / L, the content of chromium (Cr) in the sediments ranged from 20.49 to 45.78 mg / kg. The content of heavy metals Chromium (Cr) in Green Mussels ranged from <0.01 to 0.20 mg / kg. Maximum weight intake of green mussels are safe for consumption of water Trimulyo per week for women with an average body weight of 45 kg for metal Chromium (Cr) is 13.27 ± 4.78 kg per week. As for males with an average weight of 60 kg of 17.68 ± 6.37 kg per week. According to the Minister of Environment Decree 51 of 2004 Trimulyo water conditions have not categorized the heavy metal contaminated Chromium (Cr). The content of heavy metals chromium (Cr) in the sediments are well below the standards set by NOAA (National Oceanic and Atmospheric Administration) of 1999. As for the heavy metal content of chromium (Cr) in the Green Mussel showed that the clams in these waters has not been contaminated by heavy metals Chromium (Cr) according to the quality standard by the Food adulteration (metallic Contamination) Hong Kong in 1997. Pencemaran logam menjadi suatu masalah yang sangat mengancam bagi ekosistem laut. Hal ini diduga karena logam berat susah hancur dan akan terakumulasi di perairan. Penelitian ini bertujuan untuk mengetahui kandungan Kromium (Cr) dalam Air, Sedimen dan Kerang Hijau (Perna viridis) serta mengetahui batas maksimum konsumsi mingguan dan tingkat kelayakan konsumsi Kerang Hijau. Sampel diambil pada Bulan Januari 2016 di perairan Trimulyo. Penelitian menggunakan metode deskriptif. Pengambilan sampel dilakukan secara Purposive Sampling Method. Analisis kandungan logam berat menggunakan AAS. Nilai MTI (Maximum Tolerable Intact) dihitung dengan rumus MWI/Ct untuk mengetahui nilai batas maksimum konsumsi Kerang Hijau per minggu. Hasil penelitian menunjukkan kandungan Kromium (Cr) dalam air di perairan Trimulyo sebesar <0,003 mg/L, kandungan Kromium (Cr) pada sedimen berkisar antara 20,49 – 45,78 mg/kg. Kandungan logam berat Kromium (Cr) pada Kerang Hijau berkisar antara <0,01 – 0,20 mg/kg. Berat Maksimal asupan Kerang Hijau yang aman dikonsumsi dari perairan Trimulyo per minggu untuk wanita dengan berat badan rata-rata 45 kg untuk logam Kromium (Cr) adalah 13,27±4,78 kg per minggu. Sedangkan untuk laki-laki dengan berat badan rata-rata 60 kg sebesar 17,68±6,37 kg per minggu. Menurut Keputusan Menteri Lingkungan Hidup No.51 Tahun 2004 kondisi perairan Trimulyo dikategorikan belum tercemar logam berat Kromium (Cr). Kandungan logam berat Kromium (Cr) pada sedimen berada di bawah baku mutu yang ditetapkan oleh NOAA (National Oceanic and Atmospheric Administration) Tahun 1999. Sedangkan untuk kandungan logam berat Kromium (Cr) pada Kerang Hijau menunjukkan bahwa kerang di perairan tersebut belum tercemar oleh logam berat Kromium (Cr) sesuai dengan baku mutu oleh Food Adulteration (Metalic Contamination) Hong Kong Tahun 1997.